Dekatkan Mahasiswa dengan teknologi melalui pelatihan aplikasi Microsoft Office dan Google Form - Syamsiah Depalina Siregar; Ahmad Salman Farid; Sartika Dewi Harahap (Nasyatuna: Jurnal Pengabdian kepada Masyarakat, 2021)
Lecturing in the era of digital society are learn whose era is full of technological sophistication. Students are required to follow the course of technological developments. Starting from looking for learning references to college assignments. This service activity is organized by the Technical Implementation Unit of Database Information Technology (UPT TIPD) STAIN Mandailing Natal by involving students from semester 1 to semester 7. This activity is packaged in the form of training (workshop) by presenting 2 experts in their respective fields. This activity is a community service activity in the form of assistance in the introduction of learning applications through Microsoft Office applications and Google Forms, the targets of this service are students who are still blind to the use of these two important applications. Even though the benefits of mastering the application are very helpful for them in completing their lecture assignments and even for their final assignments. This service uses a service learning (SL)-based learning model development method focusing on the introduction of learning applications in the form of Microsoft Word and the use of Google Forms.